Analysis of Aromatic Rice Business Performance in Gapoktan Rimbo Jaya - Pipin Maihendry; Bambang Sumantri; Irnad Irnad (Journal of Agri Socio Economics and Business, 2019)
The purpose of this study is to analyze the revenue, cost, income, business efficiency of aromatic rice and the level of satisfaction of consumers of aromatic rice in Seluma District. The data used uses primary data in the form of data on characteristics of farmer households who are members of Rimbo Jaya Gapoktan, inputs used, production, farmer work activities and rice cultivation that produce aromatic rice, aromatic rice receipts and expenditure and marketing and consumer behaviour data. This study uses analysis of TR, TC, I and R / C, while for consumer satisfaction using IPA and CSI analysis. The results showed that the acceptance of aromatic rice farmers in Rimbo Kedui Village was Rp. 15,424,000 with an average land area of 0.68 Ha. This acceptance is high. The cost of aromatic rice farming in Rimbo Kedui Village is Rp. 7.678.392/MT/MT. The income of aromatic rice farming in Rimbo Kedui Village is Rp. 7.497.357/MT. Cost efficiency is 2.00. This means that the financing of aromatic rice farming is efficient. From the level of importance and performance of the attributes of product quality and service quality, there are no attributes that enter into quadrant I. This means that consumer expectations are in accordance with the performance given. The consumer satisfaction index value is 82.50%. This means that consumers feel very satisfied with Beras Sehat Aromatik products (BSA).